KORELASIÃÂ ANTARAÃÂ KEAKTIFANÃÂ DALAMÃÂ ORGANISASIÃÂ KEMAHASISWAANÃÂ ÃÂ DENGANÃÂ PRESTASIÃÂ BELAJARÃÂ MAHASISWAÃÂ ÃÂ - Aziz, Abdul; Sunyoto, -; Widodo, Rahmad Doni (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
TujuanÃÂ penelitianÃÂ iniÃÂ adalahÃÂ untukÃÂ mengetahuiÃÂ keaktifanÃÂ mahasiswaÃÂ dalamÃÂ organisasiÃÂ kemahasiswaan,ÃÂ mengetahuiÃÂ korelasiÃÂ antaraÃÂ keaktifanÃÂ dalamÃÂ organisasiÃÂ kemahasiswaanÃÂ denganÃÂ prestasiÃÂ belajarÃÂ mahasiswa.ÃÂ PopulasiÃÂ dalamÃÂ penelitianÃÂ iniÃÂ adalahÃÂ mahasiswaÃÂ ProgramÃÂ StudiÃÂ PendidikanÃÂ TeknikÃÂ Mesin,ÃÂ JurusanÃÂ TeknikÃÂ Mesin,ÃÂ FakultasÃÂ TeknikÃÂ UniversitasÃÂ NegeriÃÂ SemarangÃÂ angkatanÃÂ 2005,ÃÂ 2006,ÃÂ danÃÂ 2007.ÃÂ SampelÃÂ penelitianÃÂ sebanyakÃÂ 81ÃÂ mahasiswa.ÃÂ DataÃÂ dianalisisÃÂ menggunakanÃÂ korelasiÃÂ sederhana.ÃÂ HasilÃÂ penelitianÃÂ menunjukkanÃÂ bahwaÃÂ keaktifanÃÂ mahasiswaÃÂ dalamÃÂ organisasiÃÂ kemahasiswaanÃÂ tergolongÃÂ sedang.ÃÂ HasilÃÂ penelitianÃÂ iniÃÂ jugaÃÂ menunjukkanÃÂ adanyaÃÂ hubunganÃÂ yangÃÂ positifÃÂ antaraÃÂ keaktifanÃÂ dalamÃÂ organisasiÃÂ kemahasiswaanÃÂ denganÃÂ prestasiÃÂ belajarÃÂ mahasiswa.ÃÂ DariÃÂ penelitianÃÂ iniÃÂ disarankanÃÂ agarÃÂ mahasiswaÃÂ lebihÃÂ dapatÃÂ memanfaatkanÃÂ organisasiÃÂ kemahasiswaanÃÂ sebagaiÃÂ saranaÃÂ pengembanganÃÂ diri. KataÃÂ kunciÃÂ :ÃÂ keaktifan,ÃÂ organisasiÃÂ kemahasiswaan,ÃÂ prestasiÃÂ belajar.ÃÂ TheÃÂ objectivesÃÂ ofÃÂ thisÃÂ researchÃÂ areÃÂ toÃÂ identifyÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ studentÃÂ affairsÃÂ organization,ÃÂ toÃÂ findÃÂ outÃÂ theÃÂ correlationÃÂ betweenÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ theÃÂ organizationÃÂ andÃÂ theirÃÂ achievementÃÂ ofÃÂ studyÃÂ inÃÂ academicÃÂ life.ÃÂ PopulationÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ theÃÂ studentsÃÂ ofÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ program,ÃÂ MechanicalÃÂ EngineeringÃÂ department,ÃÂ FacultyÃÂ ofÃÂ Engineering,ÃÂ SemarangÃÂ StateÃÂ UniversityÃÂ yearÃÂ 2005,ÃÂ 2006,ÃÂ andÃÂ 2007.ÃÂ TheÃÂ sampleÃÂ ofÃÂ theÃÂ researchÃÂ wasÃÂ 81ÃÂ students.ÃÂ TheÃÂ dataÃÂ wasÃÂ analyzedÃÂ usingÃÂ simpleÃÂ correlation.ÃÂ TheÃÂ resultÃÂ ofÃÂ itÃÂ showsÃÂ thatÃÂ theÃÂ levelÃÂ ofÃÂ studentÃÂ activenessÃÂ inÃÂ studentÃÂ affairsÃÂ organizationÃÂ isÃÂ medium.ÃÂ ItÃÂ alsoÃÂ showsÃÂ thatÃÂ thereÃÂ isÃÂ positiveÃÂ correlationÃÂ betweenÃÂ theÃÂ activenessÃÂ ofÃÂ studentsÃÂ inÃÂ studentÃÂ affairsÃÂ organizationÃÂ andÃÂ theirÃÂ achievementÃÂ inÃÂ study.ÃÂ ItÃÂ isÃÂ sugÃ¢â¬ÂgestedÃÂ toÃÂ studentsÃÂ forÃÂ usingÃÂ studentÃÂ affairsÃÂ organizationÃÂ asÃÂ aÃÂ selfÃ¢â¬ÂdevelopmentÃÂ medium. ÃÂ Keywords:ÃÂ activeness,ÃÂ studentÃÂ affairsÃÂ organization,ÃÂ theÃÂ achievementÃÂ ofÃÂ study ÃÂ